Use of Near Infra Red Reflectance Spectroscopy (NIRS) to profile fatty acids of feeds and forages - Prasad, Kodukula V.S.V.; Ramakrishna Reddy, C.; Ramana Reddy, Y.; Varijakshapanicker, Padmakumar; Blümmel, Michael (National Dairy Research Institute, 2019)
100 food/feed and forage samples were analyzed by gas liquid chromotography for their fatty acid content and the data were used to develop NIRS calibration models and standardization for prediction of fatty acid content in different feedstuffs in a rapid, non-destructive and inexpensive manner. The coefficient of determination (R2) value for calibration and validation of saturated, trans, unsaturated, omega-3 and omega-6 fatty acids ranged between 0.56-1.0 and 0.59-0.95, respectively indicating that NIRS can be used for fatty acid profiling of different feeds with moderate (trans fatty acids) to high (saturated, unsaturated, omega-3 and omega-6 fatty acids) accuracy.